Patterns of Laryngeal Nerves Injuries Following Thyroid Surgery in Al-Imamein Al-Kadhmein Medical City (Iraqi Journal of Medical Sciences, 2021)
Background: Morbidity after thyroid surgery related to injuries to parathyroid, recurrent laryngeal nerve (RLN) and external branch of superior laryngeal nerve (EBSLN), mostly due to unawareness of the anatomical variations and lack of meticulous dissection added to that patient comorbidity and type of goiter.Objective: To assess the incidence of nerves injuries (RLN and EBSLN) and evaluation of the risk factors for nerves injuries.Methods: A prospective study included 250 patients admitted to the General Surgical Unit at Al-Imamein Al-kadhimein Medical City from the first of October 2014 to the end of October 2017. Evaluation of nerves injuries (RLN and EBSLN) with regard to thyroid pathology, types of resection, age and gender. Thyroidectomies were done by different surgical teams. Patients with recurrent goiter, prior cervical surgery and preexisting vocal cord paralysis were excluded. Vocal cords assessment was done preoperatively, intraoperatively at time of extubation and postoperatively. Patients with injury to the RLN were managed accordingly and followed up by serial examination for 6-12 month, while patients with symptoms of EBSLN injuries were followed depending just on clinical feature due to lack of diagnostic facilities.Results: There were 78 (31.2%), 172 (68.8%) male and females subsequently. The age range was (18-70) years and mean±SD was (44±11.9). Multinodular goiter was the main presentation in (168 patients), while thyroiditis was the least (6 patients). Injury to RLN was reported in 8 (3.2%) patients, 3 had unilateral and 5 had bilateral. Permanent damage documented in 2 patients. There was a significant RLN injury association with malignancy and total thyroidectomy. EBSLN injury have been reported in 55 patients (22%), it was transient in 43 patients and permanent in 12 patients.Conclusion: Nerve damage after thyroidectomy is not uncommon and affect significantly on quality of life. Careful dissection and awareness of anatomical variation is essential. Majority of injuries were transient and recovered spontaneously. Immediate intervention is not recommended unless airway compromisation ensure.Keywords: RLN, EBSLN, thyroidectomyCitation: Jaber SMA, Abdulhassan BA, Hussien HK, Al-Helfy SH. Patterns of laryngeal nerves injuries following thyroid surgery in Al-Imamein Al-Kadhmein Medical City. Iraqi JMS. 2021; 19(1): 10-17. doi: 10.22578/IJMS.19.1.2
Keywords: RLN; EBSLN; thyroidectomy